Exploring the Use of the Behavior Change Technique Taxonomy and the Persuasive System Design Model in Defining Parent-Focused eHealth Interventions: Scoping Review - Mindy Silva; E Jean Hay-Smith; Fiona Graham (JMIR Publications, 2023)
BackgroundTaxonomies and models are useful tools for defining eHealth content and intervention features, enabling comparison and analysis of research across studies and disciplines. The Behavior Change Technique Taxonomy version 1 (BCTTv1) was developed to decrease ambiguity in defining specific characteristics inherent in health interventions, but it was developed outside the context of digital technology. In contrast, the Persuasive System Design Model (PSDM) was developed to define and evaluate the persuasive content in software solutions but did not have a specific focus on health. Both the BCTTv1 and PSDM have been used to define eHealth interventions in the literature, with some researchers combining or reducing the taxonomies to simplify their application. It is unclear how well the taxonomies accurately define eHealth and whether they should be used alone or in combination. ObjectiveThis scoping review explored how the BCTTv1 and PSDM capture the content and intervention features of parent-focused eHealth as part of a program of studies investigating the use of technology to support parents with therapy home programs for children with special health care needs. It explored the active ingredients and persuasive technology features commonly found in parent-focused eHealth interventions for children with special health care needs and how the descriptions overlap and interact with respect to the BCTTv1 and PSDM taxonomies. MethodsA scoping review was used to clarify concepts in the literature related to these taxonomies. Keywords related to parent-focused eHealth were defined and used to systematically search several electronic databases for parent-focused eHealth publications. Publications referencing the same intervention were combined to provide comprehensive intervention details. The data set was coded using codebooks developed from the taxonomies in NVivo (version 12; QSR International) and qualitatively analyzed using matrix queries. ResultsThe systematic search found 23 parent-focused eHealth interventions described in 42 articles from various countries; delivered to parents with children aged 1 to 18 years; and covering medical, behavioral, and developmental issues. The predominant active ingredients and intervention features in parent-focused eHealth were concerned with teaching parents behavioral skills, encouraging them to practice and monitor the new skills, and tracking the outcomes of performing the new skills. No category had a complete set of active ingredients or intervention features coded. The two taxonomies conceptually captured different constructs even when their labels appeared to overlap in meaning. In addition, coding by category missed important active ingredients and intervention features. ConclusionsThe taxonomies were found to code different constructs related to behavior change and persuasive technology, discouraging the merging or reduction of the taxonomies. This scoping review highlighted the benefit of using both taxonomies in their entirety to capture active ingredients and intervention features important for comparing and analyzing eHealth across different studies and disciplines. International Registered Report Identifier (IRRID)RR2-doi.org/10.15619/nzjp/47.1.05